PENEGAKAN HUKUM PIDANA TERHADAP KASUS PENIPUANDALAM PENERIMAAN CALON PEGAWAI NEGERI SIPIL OLEH POLISI RESORT KOTA PEKANBARU - Bianca Berliana H; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Being a civil servant is now considered gainful employment, considered a safe and promising work in the old days. Not infrequently candidate for Civil Servants (CPNS) doing anything in order to become civil servants, be it from legal and illegal lane. The situation is put to good use by the perpetrators of the crime of fraud to do with the mode of action capable of becoming civil servants passed ID. In this case relates to the enforcement of the criminal law in cases of fraud in the recruitment of civil servants by the Police Resort Pekanbaru. The purpose of this thesis, namely; First, the enforcement of the criminal law against fraud in receipt of Public Servants by police resort city of Pekanbaru, Second; obstacles encountered in the enforcement of the criminal law against fraud in receipt of Public Servants by police resort city of Pekanbaru, Third, efforts are being made to overcome the obstacles in the enforcement of the criminal law against fraud in receipt of Public Servants by police resort city of Pekanbaru. This type of research can be classified into types of socio-juridical research, because in this study the authors conducted research on the spot directly under study in order to give a complete and clear picture of the problem under study. This research was conducted at the Police Resort Pekanbaru, while the overall population and the sample is related to the issues examined in this study, the data sources used, the primary data, secondary data and data tertiary data collection techniques in this study with the observation, interview and literature. From the research, there are three main issues that can be inferred. First, the enforcement of the criminal law in cases of fraud in the recruitment of civil servants by police resort city of Pekanbaru, that the case against ID fraud in 2012 there were 1 to 2 ID fraud perpetrators victims in 2013 there were no reports of incoming and in 2013 there were two perpetrators of fraud ID with 8 casualties. Secondly, the obstacles encountered in the enforcement of the criminal law against fraud in the recruitment of civil servants by police resort Pekanbaru is the lack of evidence of the complainant, the lack of cooperation between the witnesses and the police forces, the lack of legal awareness, Third, efforts are being made to overcome the obstacles in criminal enforcement against fraud in the recruitment of civil servants by the Police Resort Pekanbaru further clarify the evidence of the complainant, the lack of cooperation from witnesses to the police, the public should be made aware of the importance of law enforcement and do not justify any means to qualify as civil servants. Suggestions author, first, it is expected that the police are more active in combating ID fraud is a criminal offense, Second, people are more aware of the importance of law enforcement, third, society does not justify any means to be able to escape into the PNS.Key Words: Establishment - Fraud – Candidate For Civil Servants – Police Resort of Pekanbaru